Effects of oxidative weathering on Raman spectra of charcoal and bone chars: consequences in archaeology and paleothermometry - Deldicque, Damien; Rouzaud, Jean-Noël; Vandevelde, Ségolène; Medina-Alcaide, Maria Ángeles; Ferrier, Catherine; Perrenoud, Christian; Pozzi, Jean-Pierre; Cabanis, Manon (Comptes Rendus. Géoscience)
Chars are useful proxies in many disciplines such as the geosciences and archaeology. Raman spectrometry is frequently used in the characterization of such materials. However, when they are ancient and potentially altered, chars have the particularity of being oxidized, which can strongly disturb the spectra and seriously distort their interpretation. In this study, we highlight the Raman parameters affected by oxidative weathering based on comparisons between the spectra of experimental and ancient chars, of vegetal and animal origin. This makes it possible to differentiate between unweathered and weathered chars and we show that the recent methods of Raman thermometry and precursor discrimination are no longer valid when applied to oxidized chars. Nonetheless, it remains possible to estimate the formation temperature of a charcoal when some fragments are preserved at the micrometre scale. Furthermore, we propose an original tool that enable us to distinguish the vegetal or animal origin of ancient and oxidized chars. We successfully apply this new tool to charred hearth residues of the Bruniquel cave (France).